INNOVATION AND MARKET MIX ON GROWTH OF EXPORT FIRMS: EMPIRICAL EVIDENCE FROM SELECTED EXPORT FIRMS IN KENYA - AcholaOgundo, Joyce; Kibas, Peter; Otuya, Robert (International Journal of Engineering Technologies and Management Research, 2018)
The purpose of the study examined Innovation and Market Mix on Growth of Export Firms: Empirical Evidence from Selected Export Firms in Kenya. The study applied the survey research design.The target population consisted of 770 export firms registered by Export Promotion Council. The directory of Export Promotion Council was the source of data. The sample frame was stratified into seven sub-sectors, namely: agricultural, manufacturing, commercial crafts, services, mining, industrial and energy. The sample size was 169 export firms. Data was collected using structured questionnaires. The study adopted descriptive inferential data analysis and structure Equation Modelling.Findings:indicated that Innovativeness Split Model yielded Ratio Index (2.013), p<0.05 hence significant, Innovativeness Split Model has aweak significant ; Ratio index (2.224)- less than 0.5 .In comparison,Innovative and MarketingMix Models differ indicates that constraining parameters worsened on overall model fit specifically on Innovativeness.The results further yielded a percentage error difference of 10% on the Innovativeness while percentage error difference of 1 % on Marketing Mix indicating that Marketing Mix was effective than Innovativeness Model .Conclusion: Results indicate a strong relationship between Marketing Mix and Growth of Export Firms and a low correlation between Innovativeness and Growth of Export Firms .Marketing Mix loaded higher than Innovativeness in support of Growth of Export Firms.Recommendations: Firms needs to focus on Marketing Mix,to carry out training and harness further research on Innovativeness.Contribution:were MarketingMixModel_A ,Innovativeness_B and the techniques employed in testing the model are evidence to add value on researches. Agricultural, manufacturing, commercial crafts, services, mining, industrial and energy.